ANALISIS KINERJA REKSADANA SAHAM Studi Kasus Reksadana Trim Syariah Saham - , Didik Siswonagoro ([Yogyakarta] : Universitas Gadjah Mada, 2011)
TRIM Syariah Saham with Rp143,83 trillion of total Net Asset Value (in Agustus 2010) is an equity fund with the main objective to maintain principal investment and to obtain optimum return comprising capital gain and dividend in the long run in line with the Syariah capital market principles, by investing in a list of Syariah-compliant equities approved by Bapepam dan LK, or by other parties approved by Bapepam dan LK. TRIM Syariah Saham has managed by PT Trimegah Securities Tbk as Investment Manager has vision to become a leading national and international security company. PT Trimegah Securities trying to give services and investation product with international standard. TRIM Syariah Saham invest 80% to 100% in equity securities, 0% to 20% in debt securities, as well as 0% to 20% in money market instruments in in line with the Syariah capital market principles. The purpose of this research is to analyze the performance of TRIM Syariah Saham. The result of analysis shows that the performance of TRIM Syariah Saham is unfavorable as the parameters shows in negative result : Sharpe ratio = - 0,0208, Treynor ratio = - 0,1064 dan Jensen alfa = 0,1946. Furthermore, the result of analysis using Risk Adjusted Performance Measurement (RAPM) is - 0,0842 with Value at Risk at 57.919.580 (IDR) for 100 million (IDR) asset and 1 month holding period. This performance is still below performance of other competitors (PNM Ekuitas Syariah).